SOCIODEMOGRAPHIC RELATIONSHIP AND HISTORY OF CONCOMITANT DISEASES WITH CORONARY HEART DISEASE IN ACEH PROVINCE (SECONDARY DATA RISKESDAS 2018) - Naimah, Naimah; Abdullah, Asnawi; Ichwansyah, Fahmi (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: Coronary Heart Disease (CHD) in Indonesia, especially Aceh Province, is the number one contributor to death at this time. The prevalence of CHD by province at the age ? 15 years was reported that Aceh ranks in the top two with the highest CHD provinces (D 0.7% and D/G 2.3%). This research needs to be analyzed further aimed to determine the determinants of CHD in Aceh Province because CHD in Indonesia is one of the main problems most noticed by the government. Various programs to anticipate and find solutions of health problems, especially CHD has beeen made for the good of the people of Indonesia. Methods: Further analysis of this secondary data is descriptive analytic using cross-sectional design. The research location in Aceh Province was conducted in May-June 2013. The secondary data was reprocessed by researchers in 2019. The population and samples in this study were 11.617 households and 40,951 household members. Data analysis was performed using univariate and bivariate analysis. Result: The results showed that there is a relationship between age and coronary heart disease (p value 0.001), gender (p value 0.001), low education level (p value 0.002), employment status (p value 0.008), Diabetes mellitus (p value 0.001), hypertension (p value 0.001), and smoking (p value 0.0001). Recommendation: It is hoped that the provincial government implements the No Smoking Area (KTR) policy in every public area such as schools, terminals, hospitals and create qanuns that truly public health precision.